“Studi Pengaruh Beban Non Linear Terhadap Keberadaan Arus Netral Di Gedung Pusat Komputer Universitas Riau” - Yudi Adriko Putra; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Electronic equipment such as computer , scanner , printer , converter , and inverter is non - linear loads . Non - linear load is comparison with voltage and current to the review ratings time different not the same . The existence of non- linear loads on electricity system disorders will cause harmonics . The past harmonics level which is dictated standards can be causing damage to electronic equipment on that even reduced Age An electronic equipment . In the three - phase system , non - linear expenses condition unbalanced circumstances can be caused neutral currents . Objective Singer aims to review counting big losses neutral channel in sistem Three - phase non linear with loads on Computer Center Building Universitas Riau.Keywords : non linear loads, harmonics, neutral currents